Síndrome da apnéia obstrutiva do sono: diagnóstico e tratamento - Bertoz, André Pinheiro de Magalhães [UNESP] (2012)
The Syndrome Obstructive Sleep Apnea (OSA) is defined by recurrent episodes of a total or partial obstruction of the airway during sleep, considered apnea and hypopnea respectively. Considered to be increasing by increasing the number of individuals with a disorder breathing, Being continually increasing the number of individuals with a respiratory disorder, OSA can be considered a public health problem that deserves greater attention in relation to diagnoses and treatments that are being conducted. The objective of this study is through a literature review which should be evaluated during the diagnosis and etiology, consequences and treatment of respiratory disorders not adequately treated. The etiology is multifactorial and may be associated with exogenous factors or pathological and anatomical factors. In addition to the own symptoms interfere with the quality of life of the individual, depending on the intensity, OSA can trigger more serious complications. This is a complex syndrome which may have varying degrees and irreversible consequences to the body. The choice of treatment should be based on clinical conditions, the severity of the apnea, the degree of urgency of treatment and the patient's preferences, but the treatments available will not be fully effective if there are no changes in lifestyle of it. The respiratory disorders can range from a simple nasal obstruction and intermittent obstruction more severe, emphasizing the importance of a complete diagnosis, which must be multidisciplinary, through a team relationship between doctor and dentist.